Correlation between Motivation for using Social Media and Self-Regulation in Adolescents - Johan Ramadhan Nurwardan; Elis Yulia Ningsih; Dian Dian; Jatiarta Soewarta (Green Publisher, 2025)
The rapid growth of social media use among adolescents has raised questions about its psychological impact, particularly in relation to self-regulation. This study aimed to examine the relationship between motivation in social media use and self-regulation behavior in adolescents. Using a quantitative correlational design, data were collected from 204 adolescent respondents through online questionnaires. The instruments used included the Social Media Motivation Scale (Pertegel et al., 2019) and a Self-Regulation Scale based on Zimmerman’s theory of self-regulated learning. Due to the non-normal distribution of one of the variables, Spearman’s Rho correlation analysis was used. The results showed a significant positive correlation (r = 0.456, p < 0.05) between motivation in social media use and self-regulation, indicating that adolescents with stronger and more purposeful motivations for using social media tend to demonstrate higher levels of self-regulatory behavior. These findings suggest that social media, when used with clear intent, can support the development of self-regulation in adolescents. Implications for education, parenting, and further research are discussed.